Packaging Design for Buddhist Amulet of Lamphun Province by Mahawan Community Enterprise - Orkarw, Pattarakorn (Frontiers in Engineering Innovation Research, 2020)
Package design for Buddhist amulet from Mahawan community enterprise, Lamphun province has the following objectives: 1. To design the package structure to have suitable of shape, utility and costs of production, 2. To test the mechanical performance of the structure in product protection, 3. To design graphics to be attractive, remarkable with unique characteristics on the package and 4. To evaluate satisfaction form the package design. The sample were 10 of manufacturers and distributors. For the population, 100 of tourists or anyone who interested in Buddhist amulet of Lamphun province around Mahawan temple, Lamphun were selected. Use consumer behavior collecting survey method to design the package structure of 3 types consist of Anti-vibration, Impact resistance, and pressure resistance, which included cost analysis and the forming period. The result shows that Type No.3 is the most suitable due to the use of kraft paper that can be decomposed naturally therefore the packaging is environmentally friendly. It is foldable box and can be seen the product inside through the front of the box with the least of production cost and time for forming. Moreover, the brand is designed by using letters for the purpose of effective communication, with clear and easy to read that also beautiful and interesting. The graphic was depicting the Buddhist amulet of Lamphun province and Mahawan temple. The applied pattern comes from the stucco and the pattern written on the wall on the chapel of Mahawan temple. Characters that represent the northern region by using dark brown for a color digital printing method. Packaging design of Buddhist amulet of Lamphun province covers 4 areas which are: 1. Market competition, 2. Compatibility with international system, 3. Safety control, and 4. Conservation of natural resources and the environment. Overall satisfaction assessment result is very satisfied.